Liberal Governments, Authoritarian Policing: Surveillance of State Enemies in Contemporary Spain - Jiménez, Aitor; Farías, Javiera (Surveillance & Society, 2025)
Do both authoritarian and liberal-democratic regimes rely on similar forms of police governmentality and state terror to sustain public order and security? Are police forces inherently authoritarian institutions that cannot be reformed? Our aim is to explore these questions by analysing the case of Spain, a constitutional democracy considered free by liberal standards, yet where, in the short period between 2011 and 2024, the two main policing bodies in Spain—the National Police and the Guardia Civil—were involved in the legal and illegal surveillance and espionage of almost one-hundred parliamentarians from left-wing, Basque, and Catalan organisations, the questionable infiltration of “radical” and “anti-fascist” social movements, and operations to cover up widespread royal, political, and corporate corruption.